Pengembangan Aplikasi Kuliah Kerja Nyata Tematik Universitas Palangka Raya Berbasis Website - Dewi, Dian Meliani Kusuma; Lestari, Ariesta; Oktaviyani, Enny Dwi (Universitas Palangka Raya, 2021)
The University of Palangka Raya KKN-T Program (KKN-T UPR) is one of the programs from the Pillars of Higher Education (Tri Dharma College), namely Community Service. The implementation of UPR's KKN-T activities is handled by an institution, namely LPPM (Institute for Research and Community Service). So far, the management of KKN-T data in LPPM UPR has been computerized but has not been implemented in the entire data management process. The methodology used in the development of this Real Work Lecture Application is the waterfall method which has stages, namely, the Requitments Definition stage is described using a Flowchart, Requirements Analysis and Definition is described through UML (Unified Modeling Language) with Use Case Diagrams, Class Diagrams and Activity Diagrams and databases. Implementation and Unit Testing using the codeigniter framework and MySQL as well as testing using the Blackbox method. On the website that has been developed, admins can manage activity absence data, reports and log books inputted by students, manage student value data inputted by DPL, and manage user and application settings to be able to manage applications as needed. Furthermore, on the DPL side, DPL can see students who are their guidance and fill in student assessment data. Operators can also manage student data and location data as well as DPL.